Association Between Intraoperative Platelet Transfusion and Early Graft Regeneration in Living Donor Liver Transplantation. Issue 6 (December 2016) - Han, Sangbin; Park, Hyo-Won; Song, Ji Hyeon; Gwak, Mi Sook; Lee, Won Jae; Kim, Gaabsoo; Lee, Suk-Koo; Ko, Justin Sangwook
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To evaluate the association between anesthetic management before and after graft reperfusion and early graft regeneration in living donor liver transplantation (LDLT). Background: Sufficient graft regeneration is essential for the success of LDLT. Diverse signals start to trigger liver regeneration immediately after graft reperfusion. Methods: Graft volume at 14 ± 2 days after LDLT was measured in 379 consecutive recipients using computed tomography images with 3-dimensional reconstruction. The association between anesthetic variables and the degree of graft regeneration for 2 weeks was analyzed using simple and multiple linear regressions. The anesthetic variables included hemodynamics, laboratory measurements, vasoactive drugs, and blood products transfusion. Results: The degree of graft regeneration for 2 weeks was 52% in median and ranged from 5% to 123%. Platelet transfusion was identified as the sole independent anesthetic factor contributing to graft regeneration. Platelet concentrate transfusion of 1 to 6 units vs none was correlated with a 6.5% increase in graft regeneration ( P = 0.012). Platelet concentrate transfusion of more than 6 units vs none was further correlated with an 18.4% increase in regeneration ( P < 0.001). In the subgroup of recipients without intraoperative platelet transfusion, mean platelet count measured during the intraoperative reperfusion phase was positively associated with graft regeneration ( P = 0.033). Conclusions: Graft regeneration after LDLT increased in relation to a graded increase in the amount of transfused platelets and higher postreperfusion platelet counts during surgery. These results offer additional evidence regarding the important role of platelets in initiating liver regeneration and, furthermore, the indications for and the benefits vs risks of platelet transfusion during LDLT.